2012
DOI: 10.1002/adma.201200540
|View full text |Cite
|
Sign up to set email alerts
|

Path‐Guided Wrinkling of Nanoscale Metal Films

Abstract: Path‐guided wrinkling enables fabrication of defect‐free and arbitrary‐shaped wrinkle patterns. A new concept of unit‐wrinkle is introduced here, through which more complex wrinkle patterns can be quantitatively designed and realized by the processes of laser direct writing‐guided wrinkling. A simulation based on a composite film model agrees remarkably well with experimental data. Wavy‐surfaced devices are able to be produced by path‐guided wrinkling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
36
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 61 publications
(36 citation statements)
references
References 27 publications
(30 reference statements)
0
36
0
Order By: Relevance
“…As an example of a deformable artificial microstructures, we focus here on a surface with microwrinkles . Buckling of the thin surface layer supported by a compliant substrate occurs in response to an applied in‐plane compressive stress and results in periodic surface undulation, referred to here as wrinkles.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As an example of a deformable artificial microstructures, we focus here on a surface with microwrinkles . Buckling of the thin surface layer supported by a compliant substrate occurs in response to an applied in‐plane compressive stress and results in periodic surface undulation, referred to here as wrinkles.…”
Section: Introductionmentioning
confidence: 99%
“…The periodicity Λ of the wrinkles scales as Λ ∝ h ( E f / E s ) 1/3 , where h is the thickness of the surface layer, E f is the Young's modulus of the surface layer, and E s is that of the compliant substrate. Because the wrinkles form through self‐organization, they are applied for various micro‐patterning methods as low‐cost templates and other novel applications such as smart adhesive surfaces . The relationship between Λ and E f has also allowed wrinkles to be used for evaluating the hardness of very thin films .…”
Section: Introductionmentioning
confidence: 99%
“…37,38 Such textured structure with a spacer is also promising; for example, self-cleaning nanodome solar cells with a 280-nm-thick hydrogenated a-Si:H layer can absorb 94% of the light with wavelengths of 400-800 nm, which is significantly higher than the 65% absorption of flat film devices. 39 The enhancement with arrays of ridges is reminiscent of surface wrinkles and folds, [40][41][42] which are spontaneously generated by depositing a metallic film on an elastomeric substrate followed by heating. Here, the elastomeric layer can be the organic active materials, and the metallic wrinkles or folds will act as the nanostructured back contact ( Figure 5).…”
Section: Spps Induced Absorption Enhancementmentioning
confidence: 99%
“…On the other hand, direct wrinkle patterning methods were developed using a focused ion beam ( 34 ) and lasers ( 35 ) for more precise patterning of wrinkles. Although these studies demonstrated the generation of wrinkles with designed patterns that were unachievable by the other methods discussed above, these techniques are inadequate for transformation purposes.…”
Section: Introductionmentioning
confidence: 99%